Effects of cytostatic compounds on zebrafish embryos - Aires, Ana Filipa Gomes (2023)
Cytostatic drugs are a group of chemotherapeutic substances with different mechanisms of action and with a significant increase of usage. These drugs, mainly used in cancer treatment are, after their administration, excreted via the urine and/or feces of the patients being treated, and further released into the environment through hospital wastewater and/or domestic sewage. Due to the inefficiency of wastewater treatment plants, these compounds reach the environment affecting non-target animals, such as fish. Zebrafish is a biological model widely used in the study the development of vertebrates, the modeling of human diseases, such as cancer, and the evaluation of the effect of environmental contaminants. Its use in many fields of research has been increasing, given the advantages it presents in comparison to other traditional models such as mice (e.g. ease of handling, laboratory maintenance and genetic similarity with humans). This dissertation is divided into three chapters which includes a general introduction, a review article and the experimental work, and the principal aim of this work was to evaluate the physiological and biochemical as well as behavioral responses provoked by two cytostatic compounds, methotrexate and 5-fluorouracil, individually and in combination, in zebrafish, after short exposures (120h) to a range of concentrations, including environmentally relevant concentrations. Effects of both cytostatic compounds were detected in the evaluated parameters. With methotrexate these differences were detected predominantly at the highest concentration (1000 µg.L-1), while with 5-fluorouracil and the mixture there were differences in all tested concentrations. Both drugs have been shown to cause stress in the organisms and in general have caused changes in the heart level and tail of the zebrafish. This work will shed some light for the understanding of the consequences of the release of these compounds into the environment, to identify more sensitive biological responses and potential mechanisms of toxicity.